Introduction to Dossier. Twenty-First century cities: Urban public policy, displacement and contestation - Agustín Cócola Gant; Gustavo Durán; Michael Janoschka (Íconos)
Introduction to Dossier "Twenty-First century cities: Urban public policy, displacement and contestation."